(untitled) (Sains Humanika, 2025)
Part-time students face stress from juggling work, family, and studies, limited campus involvement, extended graduation time, financial issues, and job stability. Meanwhile, work-life balance is critical for reducing stress. Therefore, this study investigated the relationship between work-life balance and perceived stress among part-time students. This study employed a quantitative and cross-sectional design. The results indicated that most students reported low levels of perceived stress, with a strong negative correlation between work-life balance and perceived stress. The results suggest that improving work-life balance can have a significant impact on reducing perceived stress. Furthermore, our regression analysis revealed that perceived stress explained approximately perceived stress, with a strong negative slope indicating that increasing perceived stress is associated with decreasing work-life balance. The findings highlight the importance of work-life balance in mitigating stress among part-time students. The study’s implications suggest that educational institutions and employers can promote work-life balance to reduce perceived stress among students, ultimately improving overall well-being.